Identifying and Distinguishing Among Teachers’ Supplementary Curriculum Use Patterns Using the Lasso - Polikoff, Morgan S.; Silver, Daniel (Frontiers in Education, 2021)
Research has shown that officially-adopted textbooks comprise only a small part of teachers’ enacted curriculum. Teachers often supplement their core textbooks with unofficial materials, but empirical study of teacher curriculum supplementation is relatively new and underdeveloped. Grounding our work in the Teacher Curriculum Supplementation Framework, we use data from two state-representative teacher surveys to describe different supplement use patterns and explore their correlates. (We use RAND’s American Teacher Panel survey of K-12 ELA teachers, representative of Louisiana, Massachusetts, and Rhode Island, and Harvard’s National Evaluation of Curriculum Effectiveness survey of 4th and 5th grade math teachers, representative of California, Louisiana, Maryland, New Jersey, New Mexico, and Washington.) We find evidence of four distinct supplement use patterns. We then predict each pattern, producing sparse models using the lasso estimator. We find that teacher-, school-, and textbook-level characteristics are predictive of teachers’ supplement use, suggesting that it may be affected by structures and policies beyond the individual teacher. We recommend researchers use consistent measures to explore the causes and consequences of supplementation.